2013
DOI: 10.7314/apjcp.2013.14.7.4313
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Cervical Cancer Screening Among Japanese University Students Who Have Never Had a Pap Smear: A Qualitative Study

Abstract: Background The rate of young Japanese women attending Cervical Cancer screenings is still low. There is a lack of studies that discussed awareness, preference, and anxiety of women to HPV self-sampling. The aim was to clarify the awareness of young women who want and do not want HPV self-sampling toward improvement the rate of attending Cervical Cancer screenings. Methods We carried out the observation study by self-administered questionnaires about the awareness of HPV self-sampling with the trial in a city, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 13 publications
3
23
0
1
Order By: Relevance
“…Further, the study found that women who rated cervical cancer screening as more important carried it out more often. This finding is in agreement with previous studies (Akujobi et al, 2008;Abotchie and Shokar, 2009;Aniebue and Aniebue, 2010;Oshima and Maezawa, 2013). However, in particular in female university students from Ivory Coast, Indonesia and Pakistan, who gave a high rating of cervical cancer screening importance (mean score above 8), fewer than 5% reported cervical cancer screening practice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, the study found that women who rated cervical cancer screening as more important carried it out more often. This finding is in agreement with previous studies (Akujobi et al, 2008;Abotchie and Shokar, 2009;Aniebue and Aniebue, 2010;Oshima and Maezawa, 2013). However, in particular in female university students from Ivory Coast, Indonesia and Pakistan, who gave a high rating of cervical cancer screening importance (mean score above 8), fewer than 5% reported cervical cancer screening practice.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have investigated possible reasons for a low participation in cervical cancer screening among female university students, including ignorance of the existence of such a test, ignorance of the importance of screening or lack of risk awareness and the risk factors to the development of cervical cancer, absence of symptoms and lack of awareness of centers where such services are obtainable, and lack of motivation to get screened (Akujobi et al, 2008;Oladepo et al, 2008;2009;Abotchie and Shokar, 2009;Aniebue and Aniebue, 2010;Ghotbi and Anai, 2012;Oshima and Maezawa, 2013). Risk factors for cervical cancer include genital, syphilis/gonorrhoea history, multiple sexual partners and intercourse at an early age, chemical, dietary and life factors, cigarette smoking, barrier and oral contraceptives and poor personal hygiene (Chou 1991;Murthy and Mathew, 2000).…”
Section: Attitudes and Practice Of Cervical Cancer Screening Among Fementioning
confidence: 99%
“…Three studies noted the invasiveness of the procedure being of particular concern. [32][33][34] Male gender of physicians was also noted to impede motivation for screening in two studies. 32,35 Stigma around cervical cancer was noted in 4 studies, 23,30,33,36 with two of the studies reporting stigma around the general act of visiting a gynecologist's o ce.…”
Section: Analysis Of Notable Barriersmentioning
confidence: 99%
“…Existem algumas hipóteses para essa baixa adesão das mulheres japonesas ao programa de rastreamento, uma delas é que há apenas uma cobertura parcial dos custos do exame, ficando o restante, entre 10-30% do valor, sob a responsabilidade de pagamento da mulher atendida [12]. Oshima e Maezawa (2013) [62] realizaram um estudo com mulheres jovens universitárias buscando explicar a baixa adesão desse grupo ao programa de rastreamento, a parte das limitações de alcance do estudo, os autores observaram que havia muita relutância para realização do exame motivada por: baixo incentivo para o exame, pouco conhecimento sobre o assunto e até mesmo algo como "ciclo de não realização do exame", por exemplo, algumas participantes relataram que por não conhecerem ninguém que tivesse realizado o exame anteriormente, também não se sentiam estimuladas a realizar. Convém relatar que a verificação da baixa cobertura que o programa japonês vinha apresentando fez com que algumas províncias, a partir de 2009, passassem a distribuir cupons às mulheres com idade entre 20 e 40 anos para realização do exame citológico gratuitamente, e ainda assim, a adesão vem se mantendo baixa [62,63].…”
Section: Japãounclassified